Molariform Mesiodens in Primary Dentition - Sachin B. Mangalekar; Tajammul Ahmed; M. Zakirulla; Halawar Sangmesh Shivappa; F. B. Bheemappa; Chandrashekar Yavagal (Case Reports in Dentistry)
Mesiodens is a midline supernumerary tooth commonly seen in the maxillary arch, and incidence of molariform mesiodens in the maxillary midline is rare in permanent dentition and extremely uncommon in primary dentition. A midline supernumerary tooth in the primary dentition can cause ectopic or delayed eruption of permanent central incisors which will further alter occlusion and may compromise esthetics and formation of dentigerous cysts. This paper reports a rare case of the presence of a molariform mesiodens in the primary dentition. On clinical and radiographic examination, flaring of the primary central incisors was seen, with a molariform mesiodens consisting of multiple lobes or tubercles on the occlusal surface with the well-formed root. The treatment plan consisted of the extraction of the supernumerary tooth and regular observation of permanent central incisors for proper eruption and alignment.